Relationship between Breast Cancer Subtypes and Serum CA 15-3 Levels with the Incidence of Pleural Effusion in Breast Cancer Patients at Dr. M. Djamil General Hospital, Padang, Indonesia - Kahfi Rakhmadian; Yopi Triputra; Aulia Rahman (HM Publisher, 2023)
Background: Breast cancer is a disease that has a high incidence rate worldwide. Serum CA 15-3 levels have been used extensively as a tumor marker in breast cancer and can assist in early detection, monitoring of response to therapy, and monitoring of recurrence. This study aimed to evaluate whether there is a relationship between breast cancer subtypes and serum CA 15-3 levels with the incidence of pleural effusion in breast cancer patients at this hospital. Methods: This study was a cross-sectional observational study. A total of 176 research subjects participated in this study. Analysis of the relationship between breast cancer and CA 15-3 levels with pleural effusion was carried out univariate and bivariate using SPSS version 25. Results: The results showed that there was a significant relationship between CA 15-3 serum levels and the incidence of pleural effusion in breast cancer patients (p-value = 0.0001). There was no statistically significant relationship between breast cancer subtypes and the incidence of pleural effusion (p-value = 0.105). There was no relationship between serum CA 15-3 levels and the incidence of pleural effusion in breast cancer patients based on breast cancer subtype (p-value> 0.005). Conclusion: There is a significant relationship between serum levels CA 15-3 serum with the incidence of pleural effusion in breast cancer patients at Dr. M. Djamil General Hospital, Padang, Indonesia.